Linkage of Young Mania Rating Scale to Clinical Global Impression Scale to Enhance Utility in Clinical Practice and Research Trials - Samara, Myrto T.; Levine, Stephen Z.; Leucht, Stefan (Pharmacopsychiatry, 2022)
Introduction The Young Mania Rating Scale (YMRS) is the gold standard to assess manic symptoms of bipolar disorder, yet the clinical meaning of scores is unknown. To clinically understand and interpret YMRS scores, we examined linkages between the total and change scores of YMRS with the Clinical Global Impression (CGI) ratings.Methods Individual participant data (N=2,988) from eight randomized, double-blind, placebo-controlled trials were included. Data were collected at baseline and subsequent visits. Spearman’s correlation coefficients ρ were computed, and equipercentile linking was implemented.Results A YMRS score of 6 points corresponded approximately to ‘borderline mentally ill,’ 12 points to ‘mildly ill,’ 20 points to ‘moderately ill,’ 30 points to ‘markedly ill,’ 40 points to ‘severely ill,’ and 52 points to ‘among the most extremely ill’ patients on the CGI-S. A reduction of CGI-S by one point as well as ‘minimally improved’ on the CGI-I corresponded approximately to an absolute decrease of 4 to 8 YMRS points or a 21% to 29% reduction of YMRS baseline score whereas a reduction of CGI-S by two points and ‘much improved’ on the CGI-I corresponded to an absolute decrease of 10 to 15 points or a 42% to 53% reduction of YMRS baseline score.Discussion The current study findings offer clinicians meaningful cutoff values to interpret YMRS scores. Moreover, these values contribute to the definition of treatment targets, response, remission, and entry criteria in mania trials.
Keywords: bipolar; cutoff; response; remission criterion; interpretation; minimal clinically important difference